Dampak Audit Judgment, Skeptisme Profesional, Situasi Audit Dan Lingkup Audit Terhadap Pemberian Opini Audit - Danung Nurdiatama; Swarmilah Hariani (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2020)
The purpose of this study was to analyze the effect of audit judgment, professional skepticism, audit situation, and audit scope on the accuracy of the audit opinion. The object of this research is Principal State Financial Audit IV (AKN IV) on The Audit Board of The Republic of Indonesia. This research was conducted using a sample of as many as 80 respondents. Determinants of the sample using a purposive sampling method. The design of this research a causal relationship. Therefore, the analysis of the data used is structural equation modeling using partial least squares. The result of this research suggests that the culture of the organization and the audit judgment professional skepticism, situation audit not significant impact on the implementation of the audit opinion. While the audit scope has some positive effects significantly on the implementation of the audit opinion. This is evidenced by the results of the partial test (t-test) demonstrated the significant value of one independent variable that supports the hypothesis.